The Influence of Work Environment and Organizational Citizenship Behavior (OCB) on Employee Performance at the Department of Communication and Informatics of the Province of Bangka Belitung Islands - Rhianazala, Alzena; Budiyanto, Muhammad Nur; Iriani, Atrika (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research aims to examine the impact of the work environment and Organizational Citizenship Behavior (OCB) on employee performance within the Department of Communication and Informatics of the Bangka Belitung Islands Province. A quantitative research design with a descriptive-verificative approach was applied, utilizing questionnaires, interviews, and observations as data collection methods among Department of Communication and Informatics of the Bangka Belitung Islands Province personnel. The findings reveal that the work environment has been enhanced through office space restructuring, additional cleaning facilities, and the introduction of digital filing systems and internal applications that support smoother communication and coordination across divisions. Regarding employee behavior, the level of discipline and responsibility is generally satisfactory due to the implementation of a digital attendance system, although a few employees still demonstrate inconsistency in punctuality and task completion. Moreover, physical conditions such as temperature and noise are found to influence both the psychological and physical aspects of employee productivity. Overall, improvements in the work environment and the reinforcement of Organizational Citizenship Behavior (OCB) principles positively contribute to employee motivation, enthusiasm, and performance. Hence, sustained initiatives to establish a supportive work atmosphere and nurture a culture of collaboration are crucial for achieving optimal and long-term employee performance